Mammography use among women with and without diabetes: Results from the Southern Community Cohort Study - Maureen Sanderson; Loren Lipworth; Xijing Han; Alicia Beeghly-Fadiel; David Shen-Miller; Kushal Patel; William J. Blot; Margaret K. Hargreaves (Springer, 2019)
Studies have shown an increased risk of breast cancer associated with diabetes which may be due to differences in mammography use among women who have diabetes compared with women who do not have diabetes. Baseline data was used from the Southern Community Cohort Study - a prospective cohort study conducted primarily among low-income persons in the southeastern United States - to examine the association between diabetes and mammography use. In-person interviews collected information on diabetes and mammography use from 14,665 white and 30,846 black women aged 40-79 years between 2002 and 2009. After adjustment for potential confounding, white women with diabetes were no more likely (odds ratio [OR] 0.95, 95% confidence interval [CI] 0.85-1.06) to undergo mammography within the past 12 months than white women without diabetes. Nor was there an association between diabetes and mammography use among black women (OR 1.00, 95% CI 0.93-1.07). An increase in mammography use was seen within one year following diabetes diagnosis, more so among white than black women, but this was offset by decreases thereafter. Although there was some evidence of an increase in mammography use within one year of diabetes diagnosis, these results suggest that mammography use is not related to diabetes.